Kognitiv dissonans– vad ligger till grund för att behandla djur olika? - Lyngemark, Helena (2019)
Cognitive dissonance is a psychological concept which describes a feeling of discomfort thatcan occur when your actions differ from your feeling of what is right to do. This essay aimsto immerse in this subject due to my interest in how this phenomenon arises. The concept ofcognitive dissonance was first introduced to me when reading the book Why we love dogs, eat pigs and wear cows by psychologist Melanie Joy. To review what makes us value animals differently, I have summarized literature on the subject.